AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN LEARNING VOCABULARY IN GRADE VIII OF SMPN 3 SUNGAI LALA - Nadiya Erwinda Wulandari; Destri Wahyuningsih (Program Studi Pendidikan Bahasa Inggris, 2026)
This study aimed to analyze the difficulties faced by eighth-grade students of SMPN 3 Sungai Lala in learning English vocabulary. The research employed a descriptive qualitative approach to obtain a deeper understanding of students’ vocabulary learning problems in the classroom. The findings revealed that students experienced various interconnected difficulties, particularly in pronunciation, spelling, grammar, word form, and word usage. Among these aspects, word usage was identified as the most difficult area, followed by word form and pronunciation. The study also found that students’ vocabulary difficulties were influenced by limited exposure to English, lack of confidence, and insufficient contextual practice in using vocabulary. These findings indicate that vocabulary learning is a multidimensional process that requires more than simple memorization. Therefore, it is recommended that English teachers implement interactive and communicative teaching strategies that emphasize contextual learning, meaningful language exposure, and active vocabulary practice in order to improve students’ vocabulary mastery and classroom participation.